Mexiletine and False Positive Urine Drug Screen for Amphetamine: A Case Review - Sumit Sohal; Mina Sous; Gauri Pethe; Shanmugha V. Padmanabhan; Rajesh Akbari; Shahriar Dadkhah (Case Reports in Medicine)
Advanced heart failure patients commonly suffer from ventricular arrhythmias which can be managed by antiarrhythmic drugs like mexiletine. These ventricular arrhythmias can be complicated by illicit drug use which alter outcomes and can potentially impact the patient-physician relationship through countertransference. However, mexiletine can lead to false positive urine drug screen testing for amphetamine, and these false-positive urine drug screen test results can affect the decision-making process. Health care providers should be aware of this fact and should either use confirmatory testing or look for confounding compounds in patients who deny using illicit substances and have a positive urine drug screen. Our patient is 64 years old who arrived at the emergency department after experiencing a shock by his intracardiac defibrillator. The patient tested positive for amphetamine on his urine drug screen and was later ruled out by confirmatory quantitative testing.